(untitled) (Panacea Journal of Medical Sciences, 2024)
The consequences of infective endocarditis vary from trivial to catastrophic valvular and paravalvular destruction. The risk of IE increases with age and it is more common in men. The incidence of IE in North America and Western Europe is 1.7 – 6.2 per 100,000 person-years.We report a series of three cases of right sided infective endocarditis received at our hospital with different etiologies. In a series of three cases, we found one case of peripheral venous thrombophlebitis with Staphylococcus aureus acute endocarditis, one case of pacemaker lead subacute culture negative endocarditis and one case of subacute endocarditis with Enterococcus faecalis . The age distribution was varied with female preponderance.The three cases are presented here due to the rarity and peculiarities of presentation.